Investigation of mechanical, morphological and thermal properties of waste glass powder and wood flour reinforced polypropylene composite - Tanhim Zaman Sheikh; Foysal Ahammed Mozumdar; Md Rezaul Karim; Qumrul Ahsan (Heliyon)
The focus of this study was to investigate the potential of using waste materials like, waste glass powder and wood flour as fillers in polypropylene thermoplastic, and to assess their mechanical, morphological and thermal properties, as a means to add value to these wastes. Waste glass powder, with particle sizes of 125 μm, 63 μm, and 45 μm, was used as a filler material in the polypropylene matrix, along with wood flour particles of 250 μm in size. After identifying the optimal particle size (45 μm) sample, the WGP content was increased from 10 wt% to 15 wt% and 20 wt%. A four-step procedure was followed to create the composites, involving a kinetic mixer, sieve analysis, vacuum oven drying, and a compression molding machine. The results demonstrate that flexural strength and flexural modulus were highest in samples composed of 10 wt% and 15 wt% glass powder with a particle size of 45 μm. The tensile strength was highest in 100 wt% PP but the tensile modulus in 20 wt% glass powder with a 45 μm particle-sized sample. The maximum rebound hardness was also found in 100 wt% PP. The TGA results showed that 15 wt% WGP with a particle size of 45 μm sample was most thermally stable. A higher percentage (20 wt%) addition of waste glass powder caused non-uniform dispersion and the agglomeration of the fillers in the polymer matrix composite, which was visible in the microscopic analysis. This study found that the mechanical, morphological and thermal properties of the composite were improved by using finer particles and certain filler percentages.